A dynamic model of the Irish economy - Quinlan, P. M. (Statistical and Social Inquiry Society of Ireland, 1962)
The present paper is the result of a spare-time study over the past three years, first on the effects of increased production in agriculture on all other sectors of our economy, and more recently on the combined effects of increased production both in Agriculture and in Industry - for-Export. My interest in this problem has been continuous for a number of years and like many others I have been concerned at the high level of emigration and the reduction since the war of the numbers of those at work in Agriculture.
Read before the Society, 28 April 1961
Keywords: Dynamic model of Irish economy; Irish economic growth; Irish agriculture; Productivity in Ireland; 314.15